How Did Rumors on Twitter Diffuse and Change in Expression? An Investigation of the Process of Spreading Rumors on Twitter during the 2011 Great East Japan Earthquake. (23rd January 2019) - Ogasahara, Morihiro; Kawashima, Hirotaka; Fujishiro, Hiroyuki
Abstract : Twitter has been emerging as a major communication channels during disasters. The characteristics of Twitter—quickly and widely diffusing information and allowing every user to be an information transmitter—can be effective for problem solving in anxious and ambiguous situations such as disasters; however, false rumors on Twitter can be a serious problem. Rumor research has suggested that rumors are a kind of collective sense-making when mass media cannot provide people with enough information (e.g., during disasters). Furthermore, the expression of the rumor changes during the process of spreading. This study investigated the data of 187 thousand tweets related to the Cosmo Oil rumor during the Great East Japan Earthquake of March 2011 and analyzed the change in Twitter expressions and the collective sense-making process during this catastrophe. The results of this study suggest that collective sense-making is rare in diffused tweets, partly because of the gatekeeping role of hubs (i.e., users who have many followers on Twitter). Rumor discussion on Twitter during disasters might be suitable for broadcasting static information than for collective sense-making.